National specificity of the lexical-phraseological field Brot in the German language (linguistic-cultural aspect) - Yuriy A. Vorobyev (Этническая культура)
This article is devoted to the linguistic-cultural analysis of the background word "Brot" in comparison with its Russian conceptual equivalent хлеб in order to identify common and nationally specific differences due to the presence of cultural components on the semantic periphery of both lexemes. The lexical background of the word "Brot" is presented in the form of a lexico-phraseological field, which includes culturally marked lexical units combining both linguistic and non-linguistic content, which allowed us to interpret the background uniqueness of the lexeme in a culturally meaningful way. The relevance of the research is conditioned by the necessity of further study of the background lexicon taking into account the complex character of its non-conceptual part of meaning, possessing implicit denotative and connotative national originality, the elimination of which can have a negative impact on the act of intercultural communication. In the course of the study, we also used the methods of descriptive, comparative and component analysis, the method of critical analysis of the dictionary and dictionary definitions, which allowed us to conclude that the paradigmatic and syntagmatic relations of the word "Brot" are highly culturally unique, and revealed quantitative and qualitative differences in thematically related secondary nominations. The main material of the study is represented by culturally marked lexical units of the mentioned topics, identified by means of a continuous sampling from German explanatory, encyclopedic, phraseological and linguistic-cultural dictionaries, as well as German-Russian dictionaries.